Hubungan Antara Sense of Belonging dengan Homesickness pada Siswa Baru di Pondok Pesantren - Lestari, Mita (Al-Qalb : Jurnal Psikologi Islam, 2021)
Abstract: Homesickness is one of the negative feelings that arise when moving to a new environment. This study was carried out to the relationship between sense of belonging and homesickness in islamic boarding school students. The type of this research is quantitative with correlational quantitative design. The sample in this study was 160 new students from three Islamic boarding schools in Agam, West Sumatera. The scale used is the sense of belonging scale adapted from Hoffman, et al. (2002) and homesickness scale adapted from Yasmin (2018). The data were analysed Person Product Moment correlation. The results showed that there was a negative relationship between a sense of belonging and homesickness islamic boarding school students. With the value (r) = -0.190, (p) = 0.016 (p = 0.016 <0.05). This research can be used as input for islamic boarding school to be able to create a comfortable environment for new students so as to reduce the level of homesickness.